Pengaruh Financial Distress, Inherent Risk Dan Audit Changes Trhadap Audit Report Lag - Patricia Septin Arini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The aim of this research is to prove the influence of financial distress, inherent risk and audit changes on audit report lag. The research population used food and beverage companies listed on the ndonesian Stock Exchange for the 2019-2021 period. Sampling was taken using the purposive sampling method, resulting in 11 samples in 3 years. Data analysis is multiple linier regression. The reseach results show that financial distress han an insignificant negative effect, inherent risk has a significant positive effect and audit changes have an insignificant positive effect on audit report lag. So it can be seen that the inherent risk in the company can trigger delays in the publication of financial report.